Environmental Factors Associated with Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs, 2014)
Investigators from Taichung, Taiwan, conducted a nationwide population-based retrospective study of the association between febrile seizure (FS) and allergic rhinitis.